Sanções políticas e proporcionalidade : proteção à concorrência e regimes especiais de tributação - Santos Neto, José Leite dos (2019)
The theme of political sanctions is commonly discussed in juridical sciences only within the focus of proportionality, in the sense of precluding more forceful collections by the State. That approach revolves around the application of three classical precedents of the Brazilian Supreme Court regarding the subject (70, 323 and 547). This work proposes to go beyond that and even verify the situations in which these precedents might be set aside so that other values are not left unprotected. With this objective, this thesis initiates with the analyses of an approximated concept of fiscal justice and of the model of State that might accomplish it, the Fiscal State; this work then evolves to the study of the fundamental duty of paying taxes and, still in the first chapter, the hermeneutical method that is best suited to confront this problem. Afterward, in the matter of proportionality itself, which is already established in the scientific community as a way to measure whether a form of collection is lawful or not, this study seeks a new perspective of analysis of the subject, proving when a good is protected insufficiently. Subsequently, using the concept of political sanctions formulated by the Brazilian Supreme Court, this work demonstrates the possibility of indirect means of charging and even, as a last measure, the closing of the establishment, which incites the overcoming of the classic concept of political sanctions, at least in the specified exceptional cases. Considering the history of the theme of political sanctions and aware of the difficulties of establishing hermeneutical parameters sufficiently safe, the third chapter proceeds to study the special regimes of taxation, inspection and collection; the reach of the norm contained in the article 146-A of the Constitution and its regulation as the best suited juridical tool to establish distinctions in the normative scope of political sanctions (illicit actions perpetrated by the State) and the authorization to cancel the license to operate of companies or even to determine their closure. For this purpose, it is suggested that the legal diploma should treat the taxpayers in situation of non-payment and that belong to specific economic sectors in a proportional and gradual way, so that the most severe sanctions may only reach the debtors understood as contumacious.